Case Series: The Diversity of Cardiac Deaths in Ischemic Stroke in a Tertiary Neurology Centre - Verghese, Alice; Shanthi Viswanathan (Journal Of Cardiovascular, Neurovascular & Stroke, 2023)
Cardiac complications in brain injury is a well-documented phenomenon. The spectrum of abnormalities includes hypertension, hypotension, ECG changes, cardiac arrhythmias, release of biomarkers of cardiac injury, and left ventricular (LV) dysfunction.1 This case series is a retrospective review of the confirmed cardiac deaths over a period of twelve months in patients who were admitted to our center for ischemic stroke. Ten patients were identified as confirmed cardiac deaths out of the 76 patients who died whilst being treated for a stroke. All the patients included in this case series had at least two out of three of the following- symptoms suggestive of myocardial injury, new or evolving ECG changes and a rise in cardiac markers from baseline. Nine out of ten were males. Three were known to have a pre-existing heart condition. The management for the stroke syndrome itself is outside the scope of this review.